Echoes of research and training with biographical narratives: ways of knowing and understanding from lived experience - Leal da Costa, Conceição; Alves, Camila Aloisio; Breton, Hervé (Frontiers in Education, 2024)
This article aims to present the formative results obtained through the research-action-training device "Biographical workshop: learning about life and profession" (BW), proposed and implemented as a university extension activity in a higher education institution in Northeastern Brazil. Inspired by the epistemological and methodological bases of biographically oriented approaches in Education, the device was built with the intention of promoting, through biographical narrative, a reflective exercise both individual and collective focused on the exploration and reconstitution of personal and professional trajectories of the participants. The analyses produced from the narratives in its scope allow us to understand the different elements that give body and meaning to the trajectory of the participants in the course of their academic and professional training. Moreover, it was possible to apprehend the formative process inscribed in the mobilization of the narrative records, oral and written, and its effects for the participants. We conclude that BW is a powerful research-action-training device in that it articulates and values both the subject and the professional who is formed through lived experiences, integrating the spheres of life for an implicated, reflective and conscious professional action.